The impact of heparanase on cancer progression (Hematology Meeting Reports, 2009)
Background Heparanase is an endo-b-D-glucuronidase involved in cleavage of heparan sulfate (HS) and hence in degradation and remodeling of the extracellular matrix (ECM).1,2 Heparanase activity has been traditionally correlated with the metastatic potential of tumor-derived cell types and with cell invasion associated with autoimmunity, inflammation, and angiogenesis. The heparanase gene and protein are over-expressed in a variety of human primary tumors, including those of the bladder, breast, prostate, colon, gastrointestinal system, oral cavity, esophagous, pancreas, and ovary, as well as in multiple myeloma and acute myeloid leukemia.1,2 Heparanase upregulation is often correlated with increased tumor vascularity and poor postoperative survival of cancer patients. These observations, the anti-cancerous effect of heparanase gene silencing3 and of heparanase-inhibiting molecules4 and the unexpected identification of a single predominant functional heparanase, suggest that the enzyme is a promising target for anti-cancer drug development.